Niebo spełnieniem ludzkiej egzystencji. Szkic antropologii nieba w przekazywanym przez teologów polskich kerygmacie kościelnym w XX w. - Kucza, Grzegorz (Śląskie Studia Historyczno-Teologiczne, 2006)
Theology always serves the needs of the current teachings of the Church that are addressed to a modern man. The subject of heaven and a man destined to live in unity with God was always important in the Catholic Church’s teachings. The article looks at the question of human existence in heaven and gives the picture of it on the basis of some catechisms and sermons. As for heaven, it is the place and the state of supreme happiness and perfection, it is the perfect life in the constant presence of God. A man’s destiny in turn is to be in unity with God. The picture of ‘a man of heaven’ is created by us, by all those who live on earth whereas the fundamental task and the sole aim in life of every Christian is to ‘look for heaven’ and make it more and more real and true.